A semantic analysis of amplifiers - Škobránková, Kateřina; Kudrnáčová, Naděžda, 1956-; Masarykova univerzita. Katedra anglistiky a amerikanistiky (2006)
Práce v angličtině.
The aim of this thesis is to examine six English intensifying adverbs: absolutely, completely, entirely, fully, totally and utterly. Although they are generally regarded as synonymous, there exist semantic nuances between them. Each of the lexemes creates different collocations and is associated with a different level of subjectivity. I will concentrate on these differences and restrictions and examine the collocational ranges of the intensifiers with the help of the British National Corpus. I will include statistics of their usage and define specific semantic features of individual adverbs.
Vedoucí práce: Naděžda Kudrnáčová.
Bakalářská práce (Bc.)--Masarykova univerzita, Filozofická fakulta, 2006.
Keywords: angličtina; příslovce; synonyma; English language; adverbs; synonyms; bakalářské práce; bachelor's theses